2022
DOI: 10.1038/s41467-022-29298-1
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation of infectious Lloviu virus from Schreiber’s bats in Hungary

Abstract: Some filoviruses can be transmitted to humans by zoonotic spillover events from their natural host and filovirus outbreaks have occured with increasing frequency in the last years. The filovirus Lloviu virus (LLOV), was identified in 2002 in Schreiber’s bats (Miniopterus schreibersii) in Spain and was subsequently detected in bats in Hungary. Here we isolate infectious LLOV from the blood of a live sampled Schreiber’s bat in Hungary. The isolate is subsequently sequenced and cultured in the Miniopterus sp. kid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 67 publications
5
45
0
Order By: Relevance
“…NGS can be optimized for rapid sample preparation and real-time sequence analysis, as well as the rapid identification of certain pathogens [ 42 , 43 , 44 , 45 , 46 , 47 ]. Amplicon-based NGS sequencing is an increasingly preferred method in the rapid detection and genomic characterization of specific pathogens, with high specificity and sensitivity [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…NGS can be optimized for rapid sample preparation and real-time sequence analysis, as well as the rapid identification of certain pathogens [ 42 , 43 , 44 , 45 , 46 , 47 ]. Amplicon-based NGS sequencing is an increasingly preferred method in the rapid detection and genomic characterization of specific pathogens, with high specificity and sensitivity [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although no live ebolaviruses have been isolated from bat samples, serological and PCR data from fruit bat species in Africa support their role as reservoir hosts [9][10][11][12]. In addition, the closely related filovirus, Marburg virus (MARV), was isolated from samples from the Egyptian fruit bat, Rousettus aegpytiacus in 2007/2008 [13,14] and another filovirus, Lloviu virus (LLOV), was isolated from Miniopterus schreibersii in Hungary earlier this year [15]. In recent years, serological evidence of filovirus infection in bats has been detected in various countries including China, the Philippines, Bangladesh, Singapore, Spain, India and Trinidad [16][17][18][19][20][21][22][23].…”
mentioning
confidence: 99%
“… ( Paul, Rajagopalan and Sreenivasan, 1970 ) 23 Marburg Filoviridae, Marburgvirus yes yes yes It can be concluded that there was no evidence of vertical transmission of infection in R. aegyptiacus. Virus isolated from spleen and liver however, virus was not detected in feces or urine collected from infected specimens or the cave floor ( Towner et al., 2009 ; Leendertz et al., 2016 ) 24 Lloviu virus Filoviridea, Cuevavirus yes yes yes ( Kemenesi et al., 2022 ) 25 Yokose8 virus Flaviviridae, Flavivirus yes no yes Not associated with disease in either bats or humans ( MacKenzie and Williams, 2009 ; MacKenzie and Williams, 2009 ; Tajima et al., 2005 ) 26 Yellow fever virus Flaviviridae, Flavivirus yes no no ( Price, 1978b ) 27 Uganda S virus Flaviviridae, Flavivirus no no yes ( Lumsden, Williams and Mason, 1961 ) 28 Tamana bat virus Flaviviridae, Flavivirus yes no yes ( Price, 1978a ) 28 St Louis encephalitis virus Flaviviridae, Flavivirus yes no no Were shown to be susceptible to infection ( Sulkin et al., 1963 ; Boiro, Konstaninov and Numerov, 1987 ) 29 Sokuluk virus Flaviviridae, Flavivirus no no yes Pathogenic for suckli...…”
Section: Are Bats Viral Reservoir Animals?mentioning
confidence: 99%